Mediated learning experience: a teacher inservice training programme - Berkwitz, Gillian Helene (My University, 2016)
.There is.an urgent n1f toadd~SS ~.iedll~()n.alcrisis inSouth Africa where decades of unequal provision!! of resoJit~:jt~erkl~ black teacher training and insufficient mediation ~~Je: leftP~~pilSwith\~radl~quate ~~gnitiVe skills. Educational reform needs Inbe. rr111'fi,ensioan~drI\1uit~4f~deiru)Ttiye teacher training. I:. Ii .. 11... \ l .' I, 'Feu:erstein'lsi~~tel~prlnqjiples of med,\~ted leamil1i~ experience (MLE) were the focus. of ti,e ~c~er I~.1! .~ftVire:.F.·. . ning p~.~.:~l•).!\me w~\thl$ research aimed to implement and . ... . !i. \rn \\:' /} I"~ c \\ " evaluate. ••i ',11 . ii '. !\\ \ ." I • II 1.·.·...:.•.. 1.' ..•.•• . ",. !I 1\. \ 1/ 'II: r,\ .' . .\\ " .\ '. . . ' pou/feel! ~lidW(~~1porimary school tea~!rl;rs formed ~lhesample population for the study :1\.:~.i\;sli:;:~r:.d:.:.'n\1::e::d~~;':::N:;ti:o m;;~:~ quesll\:. ""('0}w~~. \rparticipants rated thr.. professional sell -percep~" II o\~\ ~\ . \~\\ . II \\ -. \, \'.; if The intervention dr twelve w~kly ~~~~~('!!?,~,provided theo~~tiCal'and experiential <, elaboration bf MLl~principles. Resul~~ ~~ysed on Wilcoxon Sign Rank Tests Ii c, I, ':? revealed a significan\.,increase in subJect'" ~use of four MLE principles, a decrease in ~. .~~ .' , one non-medilltional \~e'.naviour and a Signilfican1(fnCreaSe ill professional self-esteem. There was thus SUP~\1..\.£. or the..•val~e of M~f. r.-i.·ni.1If in Improving both behavioural and affective qimensio()! of ~cJ\ ••LiJ!a~~~f the study were discussed and suggestions for f'urth,er r~~~earCh'~ropo~,
A research report submitted to the Faculty of Education, in partial fulfilment of the requirements for the degree of Master of Education (Educational Psychology), University of the Witwatersrand, Johannesburg 1993.
Keywords: Teachers, Black -- In-service training -- South Africa.